Changing trends in diabetes mellitus in pregnancy. (February 2014) - Khalifeh, A.; Breathnach, F.; Coulter-Smith, S.; Robson, M.; Fitzpatrick, C.; Malone, F.
<x xml:space="preserve">Abstract</x> The purpose of this study was to identify any changing trends in the incidence and caesarean section (CS) rate of pre-gestational diabetes mellitus (DM) and gestational diabetes mellitus (GDM) over a 10- year period, between 1999 and 2008. Although the incidence of pre-gestational DM has not significantly changed over the course of the last 10 years, there is an obvious rising trend in the incidence of GDM. Despite an increase in the overall CS rate during this time period, a parallel increase in the CS rate has not been observed among women whose pregnancies are complicated either by gestational or by pre-gestational diabetes (PGD).